Windows Azure AppFabric service bus create a continuous client using Portable Class Libraries. - Kean, David (MSDN magazine)
David Kean shows how to build a simple continuous client application that spans multiple devices and platforms, using the new Portable Class Libraries and the Windows Azure AppFabric Service Bus.